2021
DOI: 10.5194/aab-64-417-2021
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the association of <i>GHR</i>/<i>AluI</i> gene polymorphisms with milk yield traits in Holstein and Jersey cattle raised in Turkey

Abstract: Abstract. This research was carried out to determine the effect of a specific single nucleotide polymorphism (SNP) region in exon 10 of the growth hormone receptor (GHR) gene on milk production traits in Jersey and Holstein cows raised in Turkey. Milk samples were recorded as a test day milk yield (TDMY) and an adjusted based 305 d milk yield (305-DMY). Also, milk component traits were detected. Based on the scope of this study, a total of 748 dairy cows, including 305 Holsteins raised in the Marmara Region an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…GHR and GDF-9 genes play a crucial role during lactation. GHR gene and its polymorphisms have a vital role in the development of the mammary gland and milk production (El-Komy et al 2020 ; Nanaei et al 2020 ; Cobanoglu et al 2021 ; Erdoğan et al 2021 ). Several studies indicated that GDF-9 increases ovarian follicles growth, and ovulation rate, and its polymorphisms had a significant correlation with litter size, number of lambs, twining %, and thus milk production (Al-Khuzai and Ahmed 2019 ; Koyun, et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…GHR and GDF-9 genes play a crucial role during lactation. GHR gene and its polymorphisms have a vital role in the development of the mammary gland and milk production (El-Komy et al 2020 ; Nanaei et al 2020 ; Cobanoglu et al 2021 ; Erdoğan et al 2021 ). Several studies indicated that GDF-9 increases ovarian follicles growth, and ovulation rate, and its polymorphisms had a significant correlation with litter size, number of lambs, twining %, and thus milk production (Al-Khuzai and Ahmed 2019 ; Koyun, et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growth hormone receptor (GHR) is involved in the regulation of postnatal growth of the body. Polymorphism in the GHR gene showed an association with milk yield traits and composition in Turkish Holstein, Turkish Jersey, and Chinese Holstein cattle [56,57]. The p.Phe279Tyr mutation in the GHR was associated with the protein percentage in the Chinese dairy population (p = 0.0014) [58].…”
Section: Candidate Genes With Predicted Functionsmentioning
confidence: 99%